IMPACT OF ROYAL SOCIETY OF CHEMISTRY-YUSUF HAMIED INSPIRATIONAL CHEMISTRY PROGRAMME IN THE DEVELOPMENT OF INNOVATIVE AND ECO-FRIENDLY MICRO-SCALE EXPERIMENTS FOR SECONDARY SCHOOL EDUCATION IN INDIA - Kandagal, P S (PEOPLE: International Journal of Social Sciences, 2019)
Science education in India faces many challenges today. Teaching practical sessions through demonstrations is one of the biggest challenges in secondary school education. Practical work in chemistry is a vital component of teaching and learning process. It is an effective way to enhance students’ understanding of science concepts and the process of scientific investigation. But most of the secondary schools in India don’t have the advantage of well-equipped labs. Specific science activities like chemistry practical may take more time than the teacher would like to spend on them. To overcome these challenges, eco-friendly micro-scale chemistry experimental kits have been developed to effectively perform the practical in secondary schools based on the existing curriculum. This paper explores the way in which the practical activities can be carried out at micro level and how the chemistry activities mentioned in secondary school NCERT textbooks can be modified using low cost and no cost materials for effective class room demonstrations.These innovative and eco-friendly micro-scale chemistry experimental kits developed through RSC-YHIC programme have been proven to be more effective in handling practical sessions, developing practical skills and empowering secondary school science teachers in India.